Implementation Of Kansei Engineering In System Appearance Design E-Learning (Case Study: Galuh Ciamis University) - Bayu Pamungkas (RISTEC : Research in Information Systems and Technology, 2024)
: E-Leaning is a primary need for carrying out teaching and learning activities, especially at universities. Galuh Ciamis University has an E-Learning called "Geulis", but the interface design is still very stiff and doesn't look comfortable when the user uses the E-Learning. Therefore, the need for user interface analysis is an important factor in using design so that it looks attractive, adjusted based on the user's needs and feelings. This research uses the Kansei Engineering method which can translate user feelings into a product design with comparison specimens from UNIGA Learning, DCI Learning Management System, My Best – Elearning BSI, Elearnig UNPER, MUCIS Learning System, E-Learning Universitas Bakti Tunas Husada E- Learning at Bakti Tunas Husada University, IAID Darussalam, and E-Learning UMC. The list of Kansei words related to web displays consists of 8 words, while the specimens used are 8 specimens which will be used as benchmarks in making the questionnaire. The participants involved in this research were 60 students at Galuh Ciamis University. It was concluded from the results of the questionnaire that there were similarities with the results of Principal Component Analysis (PCA), where in PCA there were two influential concepts which were interpreted through the x axis in the form of the "Clear" concept with a dynamic value of 0.944.